Persepsi Estetika Masyarakat Indonesia Terhadap Karya NFT Populer - Ruth Ardianti; Ely Andra Widharta (STEKOM PRESS, 2022)
This is a descriptive study that examines the Indonesian people's comprehension of NFT and the popularity of NFT (Non-Fungible Token) using qualitative and quantitative data analysis. Since the explosion of Ghozali Everyday's NFT works in Indonesia in 2021, it has been an attraction for the Indonesian people to learn